Correlation between Antifungal Susceptibilities of Coccidioides immitis In Vitro and Antifungal Treatment with Caspofungin in a Mouse Model - González, Gloria M. (American Society for Microbiology, 2001)
Caspofungin (Merck Pharmaceuticals) was tested in vitro against 25 clinical isolates of Coccidoides immitis. In vitro susceptibility testing was performed in accordance with the National Committee for Clinical Laboratory Standards document M38-P guidelines. Two C. immitis isolates for which the caspofungin MICs were different were selected for determination of the minimum effective concentration (MEC), and these same strains were used for animal studies. Survival and tissue burdens of the spleens, livers, and lungs were used as antifungal response markers. Mice infected with strain 98-449 (48-h MIC, 8 μg/ml; 48-h MEC, 0.125 μg/ml) showed 100% survival to day 50 when treated with caspofungin at ≥1 mg/kg. Mice infected with strain 98-571 (48-h MIC, 64 μg/ml; 48-h MEC, 0.125 μg/ml) displayed ≥80% survival when the treatment was caspofungin at ≥5 mg/kg. Treatment with caspofungin at 0.5, 1, 5, or 10 mg/kg was effective in reducing the tissue fungal burdens of mice infected with either isolate. When tissue fungal burden study results were compared between strains, caspofungin showed no statistically significant difference in efficacy in the organs of the mice treated with both strains. A better in vitro-in vivo correlation was noted when we used the MEC instead of the MIC as the endpoint for antifungal susceptibility testing. Caspofungin may have a role in the treatment of coccidioidomycosis.